PROCEDURAL AND INVESTIGATIVE ACTIONS RELATED TO THE INTRUSION IN TO THE HUMAN BODY AND PSYCHE: A COMPARATIVE LEGAL ANALYSIS OF REGULATION IN CRIMINAL PROCEDURE IN RUSSIA AND GERMANY - KUDRYAVTSEVA Anna Vasilyevna (Правовое государство: теория и практика, 2024)
The development of methods of research of human body and psyche influences the ways of detection and investigation of crimes by means of procedural and investigative actions, the essence of cognitive techniques of which is the intrusion into the human body and psyche. Such investigative and procedural actions include forensic medical, forensic psychiatric examination, expert certification, obtaining experimental samples from living persons for comparative research. It is obvious that these procedural and investigative actions should be regulated in a special way – with guarantees against possible harm t o human health during their conduct, as well as their validity and justification. Many problems of conducting these procedural investigative actions have not been solved in theory, legislation and practice. The purpose of the article is a comparative analysis of the norms of criminal procedure and adjacent legislation of Russia, regulating the conduct of forensic examination, expert certification, obtaining samples for comparative research from living persons, as well as German criminal procedure legislation to identify regulatory problems and propose solutions. For this purpose, the methods of comparison, description, and interpretation are used. The study concludes that there is a need for additional regulation of the procedure of forensic medical, forensic psychiatric examination, expert certification, obtaining samples for comparative research, related to the intrusion into the human body and psyche, depending on the gravity of the charge (the principle of proportionality), procedural status of the person against whom these procedural and investigative actions are carried out. The acquisition, preservation and use of human genetic code material should be particularly regulated.